Analisis Potensi Interaksi Obat Pada Resep Spesialis Penyakit Kulit di Salah Satu Klinik di Yogyakarta - Anis Febri Nilansari (Poltekkes Kemenkes Padang, 2021)
Skin diseases often occur in tropical countries, including Indonesia. Data from the Yogyakarta City Health Office showed that skin diseases were included in the top 10 diseases at the Yogyakarta City Health Center in 2020. Various types of drugs for the treatment of skin diseases, ranging from tablets, ointments, creams, pulvis and shampoos. One of the accuracy in drug selection is to avoid drug interactions. Drug-drug interaction (DDI) occurs when two or more drugs can interact in a way that affects the effectiveness of the drug. The purpose of this study is to determine the number and categories of drug interactions. This research was carried out retrospectively by taking medical data on skin diseases at one of the skin and genital clinics in the city of Yogyakarta. The data collection period is for 2 months, namely September and October 2020. The data taken are in the form of demographic data and drug use. The results showed that there were 33 cases of minor interactions. There were 21 cases of loratadine and steroids, 2 cases of ketoconazole and steroid interactions, and 10 cases of cefadroxil and acyclovir interactions. The conclusion is that offering drug combinations that allow drug interactions to occur can avoid drug combinations taken simultaneously and use only in special circumstances. It is recommended that pharmacists provide information on the rules for taking medication to maximize the effectiveness of the drug in curing the patient's illness.